2014
DOI: 10.1111/pai.12298
|View full text |Cite
|
Sign up to set email alerts
|

An observational, real‐life safety study of a 5‐grass pollen sublingual tablet in children and adolescents

Abstract: In clinical practice, pre- and coseasonal treatment with a 5-grass pollen sublingual tablet is safe and well tolerated in children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 19 publications
(29 reference statements)
1
22
0
Order By: Relevance
“…Longitudinal studies and meta-analyses in adults (112) showed that a SLIT tablet containing five-grass pollens 300-IR is well tolerated and effective in reducing AR and conjunctivitis symptoms. Studies in pediatric populations have confirmed these benefits of preand co-seasonal treatments (113,114). Significant effects were identified on symptom scores and medication scores in treated patients compared with the placebo group (115).…”
Section: Allergen-specific Immunotherapymentioning
confidence: 85%
“…Longitudinal studies and meta-analyses in adults (112) showed that a SLIT tablet containing five-grass pollens 300-IR is well tolerated and effective in reducing AR and conjunctivitis symptoms. Studies in pediatric populations have confirmed these benefits of preand co-seasonal treatments (113,114). Significant effects were identified on symptom scores and medication scores in treated patients compared with the placebo group (115).…”
Section: Allergen-specific Immunotherapymentioning
confidence: 85%
“…Non-interventional studies are, for example, suitable for investigating under real-life conditions the safety and tolerability of a drug that has been authorized for use. Two previous real-life studies have been performed with the 5-grass pollen tablet [19, 20]. These studies, one in children/adolescents and one in adults, were principally concerned with safety/tolerability.…”
Section: Introductionmentioning
confidence: 99%
“…Specially in childhood, SLIT offers practical advantages over subcutaneous therapy because injections can be avoided, the treatment is generally well tolerated [147], and the risk of severe allergic reactions seems to be negligible [148][149][150][151], even when multiple allergens [152,153] or ultra-rush and/or high-dose regimens [154,155] are used. In addition, SLIT can be administered at home rather than at a health center, thus facilitating, theoretically at least, compliance.…”
Section: Pediatric Populationsmentioning
confidence: 99%